STUNTING DAN PERANGKAP KEMISKINAN: ANALISIS MOBILITAS SOSIAL MELALUI PROGRAM CEGAH DAN ATASI STUNTING DI WILAYAH KERJA PUSKESMAS OESAPA - Yasinta Felomena Jebarus; Andreas Alfrianto Purnama; David Raden Andji; Julian Soli Bolo; Bretny Stefi Kale Bule; Lasarus Jehamat; Imelda Nahak; Balkis Soraya Tanof (Ensiklopedia Research and Community Service Review, 2026)
Abstract: Stunting is a chronic nutritional problem with medical, social, cultural, and economic dimensions. This study analyzes the role of the Stunting Prevention and Overcoming program in the Oesapa Community Health Center (Puskesmas) working area, Kupang City, East Nusa Tenggara, as a channel for social mobility to break the intergenerational poverty trap. A descriptive-analytical qualitative approach was used through in-depth semi-structured interviews with nutritionists in charge of the nutrition program, supported by passive participant observation and documentation studies. Data were analyzed using the Miles and Huberman interactive model. The results show that the two-pillar intervention preventive and curative-rehabilitative which runs in layers following the life cycle successfully reduced the prevalence of stunting significantly, from 51.7% in 2021 to below 3% in 2025. The key finding of this study is that the main obstacle is not material poverty, but rather a lack of knowledge or nutritional literacy, which accounts for approximately 95% of cases, exacerbated by the persistence of maladaptive eating practices such as the dominance of porridge as the main food for toddlers and the erosion of the culture of consuming nuts. From a sociological perspective, this program functions as a community-based human capital investment mechanism that protects children's cognitive development, transforms family nutrition literacy, and structurally contributes to breaking the intergenerational chain of poverty. The program's success confirms that nutrition interventions are not merely clinical and medical efforts, but rather social empowerment strategies that transform knowledge and parenting practices within the community. Consequently, community-based nutrition interventions can serve as a model for replication in other regions with similar socio-cultural characteristics in Indonesia. This study recommends expanding nutrition promotion through mass media, strengthening changes in cultural norms at the community level, and more integrated cross-sectoral coordination to ensure the sustainability of stunting reductions and the breaking of intergenerational poverty chains.Keywords: Stunting, Social Mobility, Nutrition, Poverty.